Characterization of Thermoplasma Species Cultured from Sampling on Tangkuban Perahu, Indonesia - AMARILA MALIK; IMAN SANTOSO; ANDI YEHUDA; SERUNI K.U. FREISLEBEN; SEPTELIA INAWATI WANANDI; HARALD HUBER; ZESSINDA LUTHFA; ROSARI SALEH; HANS-JOACHIM FREISLEBEN (Indonesian Society for microbiology, 2014)
Archaea is an organisme with unique feature because of its ability to inhabit an extremophyle conditions. Our expeditions to Tangkuban Perahu, West Java aimed to obtain archaealstrains from the solfatara fields located in Domas crater. From the samples, we intended to culture Thermoplasma species growing around 55 °C below pH 2, which until now have not yet been fully characterized. We collected five samples from mud holes with temperatures from 52 °C to 57 °C and pH below 2. In serial cultures of up to 8 transfers in Freundt’s medium we grew tetraetherlipid synthesizing Thermoplasma species as documented by phase contrast microscope. Total membrane lipid extracts were analysed by thin layer chromatography; the pattern matched total lipid extracts from Thermoplasma acidophilum DSM 1728 membranes. For confirmation, 16S rDNA identification performing PCR and sequencing were carried-out. Analysis using BLAST showed T. acidophilum identities as the highest similarity of 99%, followed by T. volcanium, also with99% similarity (ANKF776908 and ANKF776909). This is the first report of culturing cell-wall-less thermoacidophilicarchaea,in particular Thermoplasma species in Indonesian laboratories.